2020
DOI: 10.1177/1753944720977742
|View full text |Cite
|
Sign up to set email alerts
|

The subclinical hypothyroid state might predict 30-day readmission in patients admitted with acute heart failure syndrome and reduced left ventricular ejection fraction

Abstract: Introduction: Thyroid hormone (TH) has an essential role on the functional capability of cardiac muscle with its gene modulation and induction of vasodilatory effects. There is considerable evidence to suggest the role of TH in patients with acute coronary syndrome, but less is known about its prognostic role in heart failure (HF) patients. We aim to evaluate the association between subclinical hypothyroid state (SCHS) and event rates including 30-day all-cause and HF readmission in patients with an index hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, such association could not be observed with incident HFrEF. In contrast, Saad et al (2020) have reported higher readmission in 30 days and all-cause mortality in HFrEF patients with SHypo, but not in HFpEF with SHypo.…”
Section: Tablementioning
confidence: 71%
“…However, such association could not be observed with incident HFrEF. In contrast, Saad et al (2020) have reported higher readmission in 30 days and all-cause mortality in HFrEF patients with SHypo, but not in HFpEF with SHypo.…”
Section: Tablementioning
confidence: 71%